Electrochromic capacitive windows based on all conjugated polymers for a dual function smart window. Issue 8 (6th June 2018) - Kim, Younghoon; Han, Minsu; Kim, Jinbo; Kim, Eunkyoung
Abstract : A highly transparent electrochromic capacitive (ECC) window was explored by combining a high contrast electrochromic polymer (ECP) and a transparent capacitive polymer. Abstract : A highly transparent electrochromic capacitive (ECC) window was explored by combining a high contrast electrochromic polymer (ECP) and a transparent capacitive polymer. A blue and a red color ECP, poly(3, 3-bis(bromomethyl)-3, 4-dihydro-2 H -thieno[3, 4- b ][1, 4]dioxepine) (PR-Br) and poly(3, 4-di(2-ethylhexyloxy)thiophene- co -3, 4-di(methoxy)thiophene) (Th-OR), respectively, were introduced into an ECC window having a thin polyaniline (PANI) film as a capacitive layer. The as prepared ECC window showed high transparency (>72% for PR-Br), large color contrast, and long capacitive stability over 10 000 cycles, by combining non-aqueous acidic electrolyte and precise control of each electrode's working potential using in situ potential matching. Upon introducing a dielectric poly(methylmethacrylate) (PMMA) layer, the blue ECC window made of PR-Br and PANI showed bistable ECC properties, along with a high energy density of 9.7 and 13.5 W h kg −1 with a power density of 75.3 and 58.8 kW kg −1, respectively, for bleaching and coloring. The red ECC window made of Th-OR and PANI also showed a high energy density (10.5 W h kg −1 ). The energy stored in an ECC window could be transferred to another device, like a battery, to switch the color or to light a LED when the ECC window is connected in series. Thus the ECC window in this study functions as a color switching smart window and a rechargeable battery, to provide a new path to achieve energy saving EC windows with multi-color tunability. The working principle of these ECC windows can be widely applied in various electrochemical devices for multiple functions in one device.